Identification of the pore-forming and binding domains of the Sneathia vaginalis cytopathogenic toxin A. - Cathyrn K O'Brien; Jacob R Raskin; Ivypel Amankwa Asare; Christine Wei; Joy Ma; Zion T McCoy; Kimberly K Jefferson (PLoS ONE, 2023)
The association between Sneathia vaginalis and preterm birth is emerging. The Gram-negative anaerobe produces a large exotoxin, the cytopathogenic toxin A (CptA), that forms pores in human epithelial cells and red blood cells. The structure of the toxin has not been determined, but in silico analysis predicts that a large amino-terminal region of the protein is globular and separated from the carboxy-terminal tandem repeats by a disordered region. We found that a recombinant protein consisting of the predicted structured amino-terminal portion of CptA and devoid of the repeat region was sufficient to permeabilize epithelial cells and red blood cells. The repeat region was capable of binding to epithelial cells but did not permeabilize them or lyse red blood cells. CptA is the only S. vaginalis virulence factor that has been examined mechanistically to date, and this analysis sets the foundation for an understanding of how this novel pore-forming toxin exerts its activity.